Management compensation and market timing under portfolio constraints - Vikas Agarwal; Juan-Pedro Gómez; Richard Priestley (University of Cologne, Centre for Financial Research (CFR), 2012)
This paper shows that portfolio constraints have important implications for management compensation and performance evaluation. In particular, in the presence of portfolio constraints, allowing for benchmarking can be bene…cial. Benchmark design arises as an alternative effort inducement mechanism vis-a-vis relaxing portfolio constraints. Numerically, we solve jointly for the manager's linear incentive fee and the optimal benchmark. The size of the incentive fee and the risk adjustment in the benchmark composition are increasing in the investor's risk tolerance and the manager's ability to acquire and process private information.
Keywords: D81; D82; J33; 330; market timing; incentive fee; benchmarking; portfolio constraints